2021
DOI: 10.1093/ajcp/aqab018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pathology Learning Modules With Virtual Microscopy in a Preclinical Medical School Curriculum

Abstract: Objectives To evaluate the ability of pathology modules to promote learning of pathology-related course content in a preclinical medical education curriculum. Methods Pathology modules were created for the “Hematology/Oncology” and “Women’s Health” (WH) courses. Students were recruited over 2 consecutive academic years; cohorts 1 and 2 refer to 2 separate groups of students in years 1 and 2, respectively, of the study. Course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Results from various studies revealed significantly improved academic test scores [20,31,32,[36][37][38]46,48,50,52,53,58,62,63] along with improvements in the medical knowledge of students [22,34,38,[44][45][46]48,55,58,61,63,64,67].…”
Section: Vm Podcastmentioning
confidence: 99%
See 3 more Smart Citations
“…Results from various studies revealed significantly improved academic test scores [20,31,32,[36][37][38]46,48,50,52,53,58,62,63] along with improvements in the medical knowledge of students [22,34,38,[44][45][46]48,55,58,61,63,64,67].…”
Section: Vm Podcastmentioning
confidence: 99%
“…Improved student and faculty rapport [33,34,42,45,51,52,56,60] as well as better cooperation and participation amongst students was another interesting finding [20,[31][32][33][34]36,43,52,57,60,61,66,67].…”
Section: Vm Podcastmentioning
confidence: 99%
See 2 more Smart Citations
“…USF Health incorporates multiple programs (College of Medicine, Physician Assistant Program, Anatomy Masters Program), all of which use the same online histology slide viewer for normal histological education. An updated website user interface with additional instructional features will not only increase the ease of accessibility to and within the site but also improve the overall quality and efficiency of their learning [3][4][5][6][7][8][9][10]. Furthermore, the updated virtual microscopy viewer can smoothly integrate into the USF Health Morsani College of Medicine (MCOM)…”
Section: Introductionmentioning
confidence: 99%